Fire prevents woody encroachment only at higher‐than‐historical frequencies in a South African savanna. Issue 3 (25th October 2016) - Case, Madelon F.; Staver, A. Carla
Summary: Woody encroachment is a pervasive challenge facing savanna and grassland managers world‐wide. Proposed drivers of the phenomenon range from local changes in fire, herbivory and direct human impacts, to global changes in climate or atmospheric [CO2 ] that may be accelerating woody growth. The relative influences of local versus global drivers and their interactions are largely unknown, but will determine the extent to which management can limit woody encroachment locally. We examined recent woody encroachment in Hluhluwe–iMfolozi Park in South Africa from 2007 to 2014. Vegetation transects were distributed across broad gradients in rainfall, herbivore use intensity and fire frequency, on a variety of soils. Density of medium trees (2–4 m tall) increased dramatically (by 46%) in seven years, while densities of small and large trees remained constant. Increases in medium tree density were largest on sandy soils, where fires were infrequent and where grazing pressure increased. Tree density increased even where recent fire frequency was similar to historical fire regimes. These potentially widespread increases, unexplained by changes in local disturbance history, suggest the possible influence of drivers outside the scope of local control. Synthesis and applications . Fire can provide a limited buffer against generalized woody encroachment in savannas, but may only prevent further encroachment where managers can increase fire frequency. Grazing, which can limit fire frequency and intensity, may come increasingly into conflict with efforts to control woody encroachment, presenting a stark choice for savanna managers between maintenance of short‐term grazer population productivity and longer‐term prevention of woody encroachment. Abstract : Fire can provide a limited buffer against generalized woody encroachment in savannas, but may only prevent further encroachment where managers can increase fire frequency. Grazing, which can limit fire frequency and intensity, may come increasingly into conflict with efforts to control woody encroachment, presenting a stark choice for savanna managers between maintenance of short‐term grazer population productivity and longer‐term prevention of woody encroachment.